'Beauty is Truth, Truth Beauty': A Novel Account of Beauty, Bildung, and Truth in Hegel and Thomas Mann. (24th March 2021) - Casewell, Deborah
Abstract: Both Thomas Mann and G.W.F. Hegel accord beauty a particular role in their work: that of revealing truth. However, both differ in its particular stature and effectiveness. For Hegel it is an essential part of Bildung, a step to fuller knowledge of the Absolute Idea, whereas for Mann it is revelatory of the failures of Bildung, of knowledge, and self-control, and doing so it unmasks an existential truth. Drawing on Nietzsche, Schopenhauer, Lukács, and Gadamer, this article explores the way in which Mann's account of beauty, as detailed in Little Herr Friedemann and Death in Venice, challenges both Hegel's philosophy and in doing so a particular ideal of Bildung, especially with regards to its relationship to truth.